Contextual determinants of multiple sexual partnerships amongst young people in South Africa: a multilevel analysis - Nebechukwu H. Ugwu; Clifford O. Odimegwu (BMC, 2024)
Abstract Background Risky sexual behaviour (RSB), particularly multiple sexual partnerships (MSP) continues to be a major public health concern and has been linked to the increasing STIs, including HIV/AIDS in many parts of sub-Saharan Africa (SSA), suggesting that there is an association between contextual factors and multiple sexual partnering. However, in South Africa, this association is not well established in recent literature. Hence, this study examined the contextual factors contributing to multiple sexual partnerships among young people in South Africa. Materials and methods Data was extracted from the 2016 South Africa Demographics and Health Survey (2016 SADHS). A cross-sectional study of 3889 never-married young people. Descriptive and inferential statistics as well as multilevel logistic regression were used to analyse the data on never-married young people aged 15 to 24 years. Results The results indicated that at the individual level, young males (61.7%) were significantly more likely than their female counterparts (56.1%) to engage in multiple sexual partners, although, the difference was not as significant as expected. At the community level clustering, the likelihood of exposure to multiple sexual partnerships significantly increased among females (OR = 1.47; 95% CI: 1.25-1.73) but decreased among their male counterparts (OR = 0.73; 95% CI: 0.58-0.92), in particular, family disruption, residential instability, and ethnic diversity led young people to engage in multiple sexual partnerships. Conclusions There is a need to intensify programmes aimed at considering appropriate policy options to reduce the prevalence of multiple sexual partnerships. Adopting the implications of these findings is essential for a developmental strategy towards achieving the sustainable development goal of ending STIs among young people in South Africa.